2007
DOI: 10.1007/s00384-006-0261-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up after combined fissurectomy and Botox injection for chronic anal fissures

Abstract: Combined fissurectomy and Botox injection for chronic anal fissure is an excellent and safe procedure with low morbidity and a high healing rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 38 publications
1
40
0
5
Order By: Relevance
“…Among the drugs most commonly used for the pharmacological sphincterotomy, the botulinum toxin is better tolerated by patients due to high compliance associated with a low incidence of related side effects [35]. The botulinum toxin injection associated with the fissurectomy for the treatment of CAF has been reported by other authors [23,[36][37][38] with a high success rate and low morbidity. The botulinum toxin acts determining a weakness of internal sphincter with the reduction of MRP and improving the arterial blood flow in the anoderm.…”
Section: Discussionmentioning
confidence: 97%
“…Among the drugs most commonly used for the pharmacological sphincterotomy, the botulinum toxin is better tolerated by patients due to high compliance associated with a low incidence of related side effects [35]. The botulinum toxin injection associated with the fissurectomy for the treatment of CAF has been reported by other authors [23,[36][37][38] with a high success rate and low morbidity. The botulinum toxin acts determining a weakness of internal sphincter with the reduction of MRP and improving the arterial blood flow in the anoderm.…”
Section: Discussionmentioning
confidence: 97%
“…The proximal extent of LIS up to the apex of fissure, although associated with a delayed healing and increased recurrences, 16,35,61 minimizes the risk of continence disturbance. Proximal extent of LIS is particularly important in female patients because of the shorter length of the internal sphincter and vaginal deliveries that have been found to a be a significant risk factor of incontinence after LIS.…”
Section: Discussionmentioning
confidence: 97%
“…25 Fissurectomy enhances healing removing the fibrotic fissure edges, unhealthy granulation tissue at the base, and the sentinel pile when present. 25,61 Fissurectomy alone creates in essence an acute fissure with fresh wound edges, but does not address the underlying IAS spasm at the base of CAF pathogenesis. Few authors suggested that higher rates of fissure healing could be achieved if fissurectomy is combined with conservative pharmacological sphincterotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They combined local isosorbide dinitrate with fissurectomy in 15 patients and described healing rates of 100 % within a follow-up of 29 months [22]. Few recent studies [4,[23][24][25][26][27][28] To cover the exposed area after fissurectomy, an advancement skin graft has been mostly used. Only recently, a mucosal advancement flap has been used [29,30].…”
Section: Discussionmentioning
confidence: 99%